Additional value of left atrium remodeling assessed by three-dimensional echocardiography for the prediction of atrial fibrillation recurrence after cryoballoon ablation. (3rd October 2022) - Motoc, A; Scheirlynck, E; Roosens, B; Luchian, M L; Chameleva, H; Galloo, X; Von Kemp, B; De Asmundis, C; Magne, J; Droogmans, S; Cosyns, B
Abstract: Background: Atrial fibrillation (AF) is the most common cardiac arrhythmia and it is associated with a high risk of cardiovascular complications [1]. Cryoballoon ablation (CBA) has emerged as a safe and efficient therapeutic option for AF [2]. However, AF recurrence occurs in more than 25% of the patients, which leads to repeated ablations and increased rates of complications and hospitalizations [3]. Previous reports on the role of left atrial (LA) diameter and LA volume assessed by two-dimensional echocardiography (2DE) as predictors of AF recurrence after ablation have shown controversial results [4, 5]. This might be explained by the fact that these methods imply geometrical assumptions of the LA remodeling, which is a three-dimensional process [6]. Purpose: The purpose of this study was to evaluate the additional value of LA remodeling assessed by three-dimensional echocardiography (3DE) to predict AF recurrence after CBA. Methods: Consecutive patients with paroxysmal/persistent AF undergoing CBA were prospectively included. Echocardiography was performed before CBA, according to standard recommendations. Blanking period was defined as the first three months post-ablation. The primary endpoint was AF recurrence after the blanking period. Results: One hundred seventy two patients (62.2±12.2 years, 61% male) were included in the analysis. During the follow-up period of 11.7±1.6 months, fifty (29%) patients had AF recurrence after the blanking period. 3DE LA maximum volume index (LAVI) had the highest incremental predictive value for AF recurrence (HR 5.50, 95% CI 1.34–22.45, p<0.001) (Figure 1). Twenty-two percent of the AF recurrences occurred in patients with non-dilated LA diameter index and LAVI by 2DE (68 (39.5% patients)). In this category of patients, LAVI by 3DE was able to discriminate AF recurrence with a sensitivity of 90% and a specificity of 66%, for an optimal cut-off value of 30.4 ml/m 2 . Conclusion: This study showed that LAVI assessed using 3DE had an additional predictive value for AF recurrence after CBA. Moreover, LAVI by 3DE was able to discriminate AF recurrence even in patients with non-dilated LA by M-Mode and 2DE. These findings suggest that 3DE might reflect better and earlier the asymmetric and variable nature of LA remodeling and could be a potential tool in clinical practice for an improved risk stratification and pre-ablation selection of AF patients. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Universitair Ziekenhuis Brussel: Wetenschappelijk Fonds Willy Gepts of the UZ Brussel